Involvement of Cis-Acting Elements in Molecular Regulation of JH-Mediated Vitellogenin Gene 2 of Female Periplaneta americana - Elgendy, Azza M.; Mohamed, Amr A.; Duvic, Bernard; Tufail, Muhammad; Takeda, Makio (Frontiers in Physiology, 2021)
Vitellogenins are yolk protein precursors that are regulated by juvenile hormone (JH) and and/or 20-hydroxyecdysone (20E) in insects. JH acts as the principal gonadotropin that stimulates vitellogenesis in hemimetabolous insects. Herein we cloned and characterized the Periplaneta americana Vitellogenin 2 (Vg2) promoter. Multiple sites for putative transcription factors binding were predicted for the 1804 bp Vg2 promoter region, including the Broad-Complex, Ecdysone Response Element (EcRE), GATA, Hairy, Juvenile Hormone Response Element (JHRE), Methoprene (Met)-binding motif, among others. Luciferase reporter assay has identified that construct –177 bp is enough to support JH III induction but not 20E suppression. This 38 bp region (from –177 to –139 bp) contains two conserved response element half-sites separated by 2 nucleotides spacer (DR2) and is designated as Vg2RE (–168GAGTCACGGAGTCGCCGCTG–149). Mutation assay and luciferase assay data using mutated constructs verified the crucial role of G residues in Vg2RE for binding the isolated fat body nuclear protein. In Sf9 cells, a luciferase reporter placed under the control of a minimal promoter containing Vg2RE was induced by JH III in a dose- and time-dependent manner. Nuclear proteins isolated from previtellogenic female fat body cells bound to Vg2RE and this binding was outcompeted by 50-fold excess of cold Drosophila melanogaster DR4 and Galleria mellonella juvenile hormone binding protein response elements (Chorion factor-I/ Ultraspiracle). Affinity pull-down experiment with previtellogenic female fat body nuclear extracts, using 31-bp probe Vg2RE as bait, yielded a 71 kDa candidate nuclear protein that may mediate the regulatory action of the JH III.